PENGARUH PERSON ORGANIZATION FIT (X1), DAN QUALITY OF WORK LIFE (X2), BERPENGARUH TERHADAP KEPUASAN KLERJA (Y) PADA PT AGRI ANDALAS KABUPATEN SELUMA. - Fitri, Gita Septadhea Fitri (UM. Bengkulu, 2025)
This research aims to determine the influence of Person Organization Fit (X1), and Quality of Work Life (X2), on employee satisfaction (Y) at PT. Agri Andalas Seluma, either partially or simultaneously. There are several factors that will be discussed in this research, Person Organization Fit (X1), and Quality of Work Life (X2). The objects in this research are employees of PT. Agri Andalas Seluma, numbering 250 people. In this research the author used data collection methods by means of observation, interviews, distributing questionnaires or questionnaires. The data analysis techniques used in this research use instrument tests, classical assumption tests, analysis of respondent responses, multiple linear regression analysis, coefficient of determination, and also hypothesis testing. Based on the results of research that has been carried out, it is found that Person Organization Fit has a significant effect on Job Satisfaction at PT. Agri Andalas Seluma Regency, Quality of Work Life has a significant effect on Job Satisfaction at PT. Agri Andalas Seluma Regency, Person Organization Fit (X_1) and Quality of Work Life (X_2) simultaneously have a significant effect on Job Satisfaction (Y) at PT. Agri Andalas Seluma RegencyKeywords: Person Organization Fit, Quality of Word Life, Job Satisfaction.